Are remission and low disease activity state ideal targets for pregnancy planning in systemic lupus erythematosus? A multicentre study. (16th February 2021) - Tani, Chiara; Zucchi, Dina; Haase, Isabell; Larosa, Maddalena; Crisafulli, Francesca; Strigini, Francesca A L; Monacci, Francesca; Elefante, Elena; Mucke, Johanna; Choi, May Y; Andreoli, Laura; Iaccarino, Luca; et al.
Abstract: Objectives: To determine whether disease remission or low disease activity state at the beginning of pregnancy in SLE patients is associated with better pregnancy outcome. Methods: Pregnancies in SLE patients prospectively monitored by pregnancy clinics at four rheumatology centres were enrolled. Patient demographics and clinical information were collected at baseline (pregnancy visit before 8 weeks of gestation) including whether patients were in remission according to the Definition of Remission in SLE (DORIS) criteria and and/or Lupus Low Disease Activity State (LLDAS). Univariate and multivariate analysis were performed to determine predictors of disease flare and adverse pregnancy outcomes (APOs) including preeclampsia, preterm delivery, small for gestational age infant, intrauterine growth restriction and intrauterine fetal death. Results: A total of 347 pregnancies were observed in 281 SLE patients. Excluding early pregnancy losses, 212 pregnancies (69.7%) occurred in patients who were in remission at baseline, 33 (10.9%) in patients in LLDAS, and the remainder in active patients. Seventy-three flares (24%) were observed during pregnancy or puerperium, and 105 (34.5%) APOs occurred. Multivariate analysis revealed that patients in disease remission or taking HCQ were less likely to have disease flare, while a history of LN increased the risk. The risk of APOs was increased in patients with shorter disease duration, while being on HCQ resulted a protective variable. An almost significant association between complete remission and a decreased risk of APOs was observed. Conclusions: Prenatal planning with a firm treat-to-target goal of disease remission is an important strategy to reduce the risk of disease flares and severe obstetric complications in SLE pregnancies.